2020
DOI: 10.1016/j.apor.2020.102105
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical investigation of a U-shaped oscillating water column wave energy device

Abstract: Hydrodynamic performance of a fixed U-shaped Oscillating Water Column (U-OWC) Wave Energy Converter is numerically investigated. Based on the timedomain higher-order boundary element method (HOBEM), a two-dimensional fully nonlinear numerical model is implemented to simulate the nonlinear wave interaction with a U-OWC device. In the model, the inner-domain-source method is adopted to generate the incident waves and a linear pneumatic model is used to determine the air pressure which is imposed on the free surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Thus, the pressure can be computed by truerightp=ρgzρϕtρ2false(ϕfalse)2.Currently, only a few software packages are based on the FNPF theory, for example, the high‐order boundary element method of Ning et al . [104, 105]. Further assuming the wave height is much smaller than the wavelength (Hλ) and the device motion is small, linear potential flow (LPF) theory can be applied to solve the Laplace and linear Bernoulli equations in Figure 6.…”
Section: Wave Energy Technology Principlesmentioning
confidence: 99%
“…Thus, the pressure can be computed by truerightp=ρgzρϕtρ2false(ϕfalse)2.Currently, only a few software packages are based on the FNPF theory, for example, the high‐order boundary element method of Ning et al . [104, 105]. Further assuming the wave height is much smaller than the wavelength (Hλ) and the device motion is small, linear potential flow (LPF) theory can be applied to solve the Laplace and linear Bernoulli equations in Figure 6.…”
Section: Wave Energy Technology Principlesmentioning
confidence: 99%
“…The chamber and the duct together form a U-shaped duct. This has a natural period of oscillation which can be matched to that of the incoming waves to optimise energy production [19][20][21][22]. Experimental tests on a model placed in the natural laboratory of Reggio Calabria (Italy) achieved a maximum 66% wave power absorption under resonant conditions.…”
Section: Oscillating Water Column Wecsmentioning
confidence: 99%
“…[10], where it was shown that the U-OWC configuration exhibited enhanced hydrodynamic performance compared to the traditional OWC, or to the L-shaped OWC. Moreover, the performance of the U-OWC is strongly dependent on its geometrical characteristics [11,12], such as the length and the width of the U-duct, the position of its opening below the mean water level, and the width and height of the inner chamber. Further, the optimal selection and control of the Power Take-Off (PTO) system is critical for maximizing the amount of converted energy [13].…”
Section: Introductionmentioning
confidence: 99%